Tata Kelola Madrasah Dalam Meningkatkan Mutu Kerja Guru Di Massa Pandemi Covid 19 Pada Madrasah Aliyah Swasta Al Fuad - Alamsyah (Formosa Journal of Science and Technology, 2022)
This study describes madrasa governance in improving the quality of teacher work during the COVID-19 pandemic at Al Fuad private madrasah Al Fuad. The purpose of this research is to educate readers and madrasa teachers so that they always improve the quality of teacher work during the COVID-19 outbreak. This type of research is a qualitative research that seeks to explain social phenomena that are developing in the present mass. The data collection technique he did was observation and unstructured interviews and then the data was analyzed objectively and then described scientifically by following the procedures for writing scientific papers, from the results of this study it was found that: First, the madrasa leadership determined the teacher's attendance schedule as much as 50% every day and limiting working time in madrasas according to the instructions from the Covid 19 task force and then adjusting the subject matter according to the curriculum set by the government. Second, madrasa leaders conduct training for teachers in making lesson plans and learning models by utilizing social media technology. Third, madrasa leaders supervise teachers in the form of monitoring online learning processes and student assessment lists according to student competencies, Fourth, not conducting gathering activities in the madrasa environment so as not to become a cluster of Covid 19 transmission. Fifth, madrasa leaders evaluate the work of teachers every month by implementing strict health protocols.